Urban Living Labs in fostering the connection of communities with nature - Moyano Morán, Gina (Scripta Mundi, 2024)
This essay seeks to encourage the conversation about Urban Living Labs in generating or strengthening the connection of human beings with nature. The relationship between mankind and nature in various instances, as well as the factors that have influenced in the disconnection are analyzed. Then, some proposals for reconnection are mentioned, such as the ecosystem perspective and ecocentrism; this as a context for the detailed analysis of the Urban Living Labs. Thus, the characteristics and potential of the Urban Living Labs for the reintegration of human beings with nature are detailed from individual and collective collaborative perspectives.
Keywords: Urban Living Labs; reconnection; nature; sustainability